Translanguaging in the era of digital nomadism: a sociolinguistic perspective on voluntary mobility in Europe - Novella Tedesco (Discover Global Society)
Abstract Europe is experiencing a rise in mobility characterized by a greater degree of agency compared to previous internal migratory trends. Voluntary displacement is becoming increasingly common in work-related migration, also thanks to the spread of digital work. The Covid-19 lockdowns have reshaped our perception of movement, normalizing remote work and virtual collaboration. After the pandemic, more and more professionals have opted for remote-working and a new category of mobile subjects has appeared, often referred to as digital nomads, i.e. professionals who work remotely while travelling. Specifically focused on the European context, this study undertakes a sociolinguistic perspective to investigate linguistic attitudes and behaviours characterizing digital nomad communities, here presented as newly-rising online and local networks of transcultural encounters. The transdisciplinary theoretical framework here proposed asserts the relevance of translanguaging theories for a deeper understanding of the complex sociolinguistic systems characterizing digital nomad communities. Then, by undertaking a mix of quantitative and qualitative methodologies, the paper provides first insights into transcultural communicative practices, linguistic behaviours and attitudes within digital nomad communities. The results of the study highlight new mechanisms of cultural resilience, agency and self-empowerment characterizing these new types of mobile identities, which encompass an innovative use of language in pluricultural communicative contexts.